PENERAPAN POLA ASUH OTORITER ORANG TUA PADA PRESTASI BELAJAR SISWA DI MIS RAUDLATUL HASAN WONOMERTO - Mukarromah, Faizatul; Fadilah, Yulina; Khosiah, Nur (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research applies Qualitative Field Research, in this case there are several stages, namely: planning, implementation, observation, and data analysis stages. The reason the author made the journal